1999
DOI: 10.1007/s004670050677
|View full text |Cite
|
Sign up to set email alerts
|

Clinical behavioral problems in day- and night-wetting children

Abstract: In this prospective, clinical study of 167 consecutive wetting children, the associations between specific forms of day and night wetting and clinical behavioral symptoms according to a parental questionnaire (Child Behavior Checklist; CBCL), as well as ICD-10 child psychiatric diagnoses are analyzed. For the entire group, the proportion of children with at least one ICD-10 diagnosis was 40.1% and for the CBCL total problems scale 28.2% - three times higher than in the general population. Expansive disorders (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…In cases of nonmonosymptomatic enuresis, however, some studies have shown that this does not occur, with the frequency of enuresis tending to remain the same in older children, possibly as a consequence of the mechanisms involved in overactive bladder (11, 12, 15). Accordingly, the present study also failed to detect any reduction in enuresis with increasing age in non-monosymptomatic enuresis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of nonmonosymptomatic enuresis, however, some studies have shown that this does not occur, with the frequency of enuresis tending to remain the same in older children, possibly as a consequence of the mechanisms involved in overactive bladder (11, 12, 15). Accordingly, the present study also failed to detect any reduction in enuresis with increasing age in non-monosymptomatic enuresis.…”
Section: Discussionmentioning
confidence: 99%
“…Non-MSE is more commonly associated with urinary tract infections (UTI), vesicoureteral reflux, constipation and behavioral problems (11, 12). Parents often believe that their child's treatment has failed entirely when enuresis persists even though complete resolution of LUTS was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…We talk about primary enuresis when a child older than 5 years continues to wet bed during the sleep and there are no other diseases of the nervous, urogenital and endocrine systems detected [3]. It is estimated that 80% of children with nocturnal enuresis have this form.…”
Section: Definition and Classificationsmentioning
confidence: 99%
“…Moreover the risk of psychosocial comorbidity is higher in therapy-resistant enuresis 11. Refractory NE is defined as less than 50% improvement in symptoms with an adequate trial of treatment (3 months) 12…”
Section: Introductionmentioning
confidence: 99%